Financial asset - Roh, Ekaterina; Trygub, Inna (My University, 2014)
Financial assets are intangible assets. Financial assets serve two main economic functions. Financial asset is typically given a maturity date in a contractual claim. Cashing out an asset before its maturity date can ultimately cost a person financial penalties because it violates the terms of the agreement.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; financial asset; cash; person; money; stock; фінансовий актив; готівка; гроші; финансовый актив; наличность; особа; деньги; запас